Electrified Powertrains for a Sustainable Mobility: Topologies, Design and Integrated Energy Management Strategies - Tribioli, Laura; Villani, Manfredi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue was intended to contribute to the sustainable mobility agenda through enhanced scientific and multi-disciplinary knowledge to investigate concerns and real possibilities in the achievement of a greener mobility and to support the debate between industry and academic researchers, providing an interesting overview on new needs and investigation topics required for future developments.